Eight Parental Strategies for Educating the Superior Generation in Muslim Families - Elfira, Ninil; Roza, Ardino; Rasdiany, Apriana Nofriastuti; Wulandari, Ratna (El-Rusyd, 2023)
Children are the next generation who are expected to excel in everything, so Islam requires all parents to prepare and educate this generation as well as possible. This research aims to analyze parents' strategies for educating superior generations in Muslim families. This research uses a qualitative approach. The analytical method used in this research is method library research. The analysis is carried out carefully, critically and sharply so as to produce a synthesis that is logical and rational and can be tested.  The results of the study show that there are eight strategies that parents use in educating children to become a superior generation, namely: be a role model for children, take time to discuss things with children, give the same love to children, fulfill children's rights, always pray for children, avoid praying bad things for children, get children used to doing good, and avoid despicable traits. The findings found eight parental strategies in preparing and educating a superior generation in Muslim families.